Evaluation of Probation Implementations in Training and Research Hospital - Aslan, Murat; Hocaoğlu, Çiçek (The Bulletin of Legal Medicine, 2015)
Objective: Probation implementation means criminals serve their sentences under surveillance and control inside the society instead of being sent to prison as a result of an imprisonment verdict given by a judge after they commit a crime. According to this, it can be said that probation is a kind of an execution system. It is aimed to evaluate the socio-demographic characteristics of the people who applied to our hospital within probation law and the treatment coherence of the cases according to the results of probation implementation. Materials and Methods: Two hundred cases, applying to Recep Tayyip Erdoğan University, Training and Research Hospital, all of whom were decided to have probation implementation on 01.04- 15.11.2013 were included in the study. These cases consist of people, 13 of whom were from prison and 187 of whom were living out in the society. Probation implementation was carried out by having psychiatric interview and evaluating psychoactive substance in urine in three-week and six-week programs. On the other hand, the cases sent for mental evaluation were monthly followed in a period defined by probation implementation branches. Results: It was determined that totally 200 cases applied as required by Probation implementation during the study. Two of the cases were female, while 198 of them were male. Mean age was determined as 32.5 ±9.8 (18-69). It was also observed that 64 cases (23.0%) completed three week program and ten cases (5.0%) completed six week program, but twenty five cases (12.5%) showed in congruity to the treatment. Sixty-four...